Understanding statistics in the behavioral sciences - Pagano, Robert R. (Thomson Higher Education, 2007)
"Based on author Robert Pagano's 30 years of successful teaching experience, this text focuses on ideas rather than just numbers, ensuring that you never lose sight of the concepts that lie at the heart of sound statistical reasoning. Even students who are not mathematically inclined have praised this text for its clarity, interesting examples, and use of humor. Thorough explanations precede the introduction of every formula. The exercises that immediately follow include a step-by-step model that lets you compare your work against fully solved examples. Graphs, cartoons, and other visual aids help to illustrate difficult concepts while making them easier to remember. It's a combination that has worked for thousands of students who are taking their first statistics course in the behavioral sciences. Book jacket."--Book jacket.